Discovery Learning Model as an Effort to Improve Students' Understanding - Jefry Ebwantoro (SCHOOLAR: Social and Literature Study in Education, 2025)
This study aimed to determine the effect and improvement of Class X students’ understanding of the concept of energy through the Discovery Learning approach at Public Senior High School 1 Mojoagung Jombang. The research used one Group Pre-test and Post-test Design. The population of this study consisted of students in class X-1 at Public Senior High School 1 Mojoagung Jombang. The sample was taken from class X-1 at Public Senior High School 1 Mojoagung Jombang. Data collection techniques in this study involved administering pre-tests and post-tests. The research instrument used was a 10-item multiple-choice test. Data analysis was performed using prerequisite tests and N-gain tests. The results of the study indicated that the average N-Gain score in this study was 0.51, which fell into the moderate category. The conclusion of this study showed that the Discovery Learning approach could improve the understanding of energy concepts among Class X-1 students at Public Senior High School 1 Mojoagung Jombang.